HUBUNGAN BIOFILM STREPTOCOCCUS MUTANS TERHADAP RESIKO TERJADINYA KARIES GIGI - Fatmawati, Dwi Warna Aju (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
Bacteria in oral cavity are associated with oral health, as well as with dental caries. Cariogenic streptococci depend on a biofilm lifestyle for survival and persistence in the oral cavity. Primary factors allowed tooth caries is Streptococcus mutans colonization on tooth biofilms. Biofilm formation depend on carbohidrat diet n some enzyme that produced by Streptococcus mutans. It will enhance oral environment to be acid and causes tooth demineralization.